A study on the factor that contribute to the satisfaction of the customer towards the services that is provided by Telekom Malaysia (Seremban Branches) for the C&B (Consumer & Business) Units / Mohd Nazrul Ikram Baharon - Saharon, Mohd Nazrul Ikram (Faculty of Business and Management, 2004)
In this new era of telecommunication services, Telekom Malaysia has to face the challenge as equal with the growth of telecommunication technology in Malaysia. This challenge not only comes from the high competitive rivals, but also to cope and fulfill the customers expectation and demand that always become higher from time to time. Consumer & Business department is a part of Telekom division that been establish to face all of this challenge to ensure that all of the consumer demand and expectation can be fulfill and also to face the challenge that come from the competitors. And to carry such important task, this division is divided into four different departments which is Customer Retention, Customer Care, Direct Sales and Marketing Planning, each will carry a special task from increase the sales till providing the services after sales. Without the effort of this department, it is very hard for Telekom Malaysia to survive in the long run since this four department is responsible in carrying the most important task for Telekom, that is to gain sales and generate profit.